Health Challenges of the Pacific Region: Insights From History, Geography, Social Determinants, Genetics, and the Microbiome - Horwood, Paul F.; Tarantola, Arnaud; Goarant, Cyrille; Matsui, Mariko; Klement, Elise; Umezaki, Masahiro; Navarro, Severine; Greenhill, Andrew R. (Frontiers in Immunology, 2019)
The Pacific region, also referred to as Oceania, is a geographically widespread region populated by people of diverse cultures and ethnicities. Indigenous people in the region (Melanesians, Polynesians, Micronesians, Papuans and Indigenous Australians) are over-represented on national, regional and global scales for the burden of infectious and non-communicable diseases. Although social and environmental factors such as poverty, education and access to health-care are assumed to be major drivers of this disease burden, there is also developing evidence that genetic and microbiotic factors should also be considered. To date, studies investigating genetic and/or microbiotic links with vulnerabilities to infectious and non-communicable diseases have mostly focused on populations in Europe, Asia and USA, with uncertain associations for other populations such as indigenous communities in Oceania. Recent developments in personalised medicine have shown that identifying ethnicity-linked genetic vulnerabilities can be important for medical management. Although our understanding of the impacts of the gut microbiome on health is still in the early stages, it is likely that equivalent vulnerabilities will also be identified through the interaction between gut microbiome composition and function with pathogens and the host immune system. As rapid economic, dietary and cultural changes occur throughout Oceania it becomes increasingly important that further research is conducted within indigenous populations to address the double burden of high rates of infectious diseases and rapidly rising non-communicable diseases so that comprehensive development goals can be planned.